Impact of TR34/L98H, TR46/Y121F/T289A and TR53 Alterations in Azole-Resistant Aspergillus fumigatus on Sterol Composition and Modifications after In Vitro Exposure to Itraconazole and Voriconazole - Rose-Anne Lavergne; Marjorie Albassier; Jean-Benoît Hardouin; Carlos Alvarez-Moreno; Fabrice Pagniez; Florent Morio; Patrice Le Pape; Isabelle Ourliac-Garnier (Microorganisms, 2022)
Background: Sterols are the main components of fungal membranes. Inhibiting their biosynthesis is the mode of action of azole antifungal drugs that are widely used to treat fungal disease including aspergillosis. Azole resistance has emerged as a matter of concern but little is known about sterols biosynthesis in azole resistant Aspergillus fumigatus. Methods: We explored the sterol composition of 12 A. fumigatus isolates, including nine azole resistant isolates with TR34/L98H, TR46/Y121F/T289A or TR53 alterations in the cyp51A gene and its promoter conferring azole resistance. Modifications in sterol composition were also investigated after exposure to two azole drugs, itraconazole and voriconazole. Results: Overall, under basal conditions, sterol compositions were qualitatively equivalent, whatever the alterations in the target of azole drugs with ergosterol as the main sterol detected. Azole exposure reduced ergosterol composition and the qualitative composition of sterols was similar in both susceptible and resistant isolates. Interestingly TR53 strains behaved differently than other strains. Conclusions: Elucidating sterol composition in azole-susceptible and resistant isolates is of interest for a better understanding of the mechanism of action of these drugs and the mechanism of resistance of fungi.